Numerical Investigation of Rotating Lid-driven Cubical Cavity Flow - Kumar, Jitendra; Panchapakesan, N.R. (Defence Science Journal, 2017)
The present work numerically investigates the flow field in a cubical cavity driven by a lid rotating about an axis passing through its geometric center. Behaviour of core flow and secondary vortical structures are presented. Grid-free critical Reynolds number at which flow turns oscillatory is estimated to be 1606. This differs significantly from the linear lid-driven cubical cavity as well as circular lid-driven cylindrical cavity flows which have been reported to attain unsteadiness at higher Reynolds numbers. A stationary vortex bubble similar to rotating lid-driven cylindrical cavity flow has been observed to be present in the flow.